2008
DOI: 10.1007/s12185-008-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman’s disease presenting with multiple nodes in lungs: a case report and literature review

Abstract: We report a rare multicentric Castleman's disease case whose lung manifestation is severe than any known report. This is a 64-year-old woman, she had repeated cough, fever and breathlessness for more than 1 year. CT imaging showed multiple small nodules in both the lungs at the first onset. Large nodes and masses in both the lungs evolved 1 year later. After three times of lung biopsies (one video-assisted thoracoscopic surgery and two CT-guided percutaneous transthoracic), she was finally diagnosed as multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Interestingly, 2 of them predominantly had lung abnormalities. Although the clinical presentation is atypical for iMCD, similar cases have been reported [ 7 , 8 ]. These cases did not meet the diagnostic criteria for iMCD because lymphadenopathy at multiple sites is essential for the diagnosis [ 13 ].…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, 2 of them predominantly had lung abnormalities. Although the clinical presentation is atypical for iMCD, similar cases have been reported [ 7 , 8 ]. These cases did not meet the diagnostic criteria for iMCD because lymphadenopathy at multiple sites is essential for the diagnosis [ 13 ].…”
Section: Discussionsupporting
confidence: 52%
“…Common radiological pulmonary findings noted in Castleman's disease are diffuse bilateral interstitial pneumonitis with bilateral reticular opacities, bronchovascular thickening and sub pleural nodules, accompanied by dyspnea, cough, fever and lymphadenopathy night sweats and weight loss. Pleural effusions, isolated mediastinal lymphadenopathy, solitary and multiple pulmonary nodules as the presenting feature of MCD have also been described [8][9][10].…”
Section: Discussionmentioning
confidence: 97%
“…[ 1 ] After Barrie et al [ 13 ] reported on MCD-DPLDs, they have been discussed occasionally. [ 1 , 5 , 14 16 ] In the reported cases of non-HIV MCD-DPLDs, LIP-like patterns are the most commonly reported, either in radiological or pathological studies. [ 4 , 5 , 13 , 14 ] However, this same trend was not found in our enrolled CD patients.…”
Section: Discussionmentioning
confidence: 99%